Outcome of Coronary Artery Bypass Graft Surgery with Low Preoperative Ejection Fraction - Hasan, Md. Sharif; Siraj, Masoom; Rahman, Hamidur; Amin, Md. Nurul (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 20-23 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13547